ANALISIS TINGKAT KEPUASAN WISATAWAN NUSANTARA DI MUSEUM BENTENG VREDEBURG YOGYAKARTA - , ANGGRIANA EZRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tourism is an activity that can not be separated from human life. Everyone needs to travel, tourism activities can be done inside or outside of their area. There are various types of tours that we know, such as nature tourism, educational tourism, historical tourism, and the others. Historical tourism can be defined as a tourism activities that aim to enjoy and learn the history through various relics contained in a particular area. The purpose of this paper is to know the level of tourists satisfaction, especially domestic tourists in Vredeburg Museum. After the level of tourist satisfaction was discovered, it is expected that the administrators of Vredeburg Museum can further improve the quality of facilities and service so the tourists feel more comfortable when traveling in Vredeburg Museum.